Peran Pemilih Pemula dalam Pemilu 2024 - Elen Pitria; Della Utari; Yesi Marseta; Moneka Tiara Sari; Rizky Ayomi Pangestu (Pusat Riset dan Inovasi Nasional, 2023)
In 2024 Indonesia will hold elections to elect the DPR, DPRD, president and deputy, president and DPD. The lack of awareness in understanding democracy and the low level of political education for first-time voters can certainly reduce the level of voter participation in the upcoming 2024 election. Given the importance of the participation of first-time voters in the upcoming elections, it is necessary to conduct knowledge dissemination and studies on first-time voter participation in youth in Pusar Village, West Baturaja District. In this research, doctrinal or normative research methods are used through an approach to laws and regulations (statute approach), and a conceptual approach (conceptual approach). The target of this service is first-time voters who already have the right to vote in accordance with statutory regulations. The results of this socialization and service are expected to be able to provide stimulation to election voters to be actively involved in the five-year democratic party (Election) and beginner voters can have maximum readiness in making choices and know the importance of elections in the course of this nation's democracy. And secondly, you can make choices according to your conscience and you can see the candidate's track record, character factors (honest, trustworthy, populist, and have never been involved in a legal case).